A comparative study between condensed polytetrafluoroethylene mesh versus other composite meshes in Endo-laparoscopic ventral herniorrhaphy - Meredeth Chin; James Lee Wai Kit; Sujith Wijerathne; Avelyn Aw; Daryl Chia Kai Ann; Sean Lee Kien Fatt; Tharun Ragupathi; Harry Ng Ho Man; Davide Lomanto (Asian Journal of Surgery)
Introduction: Laparoscopic ventral hernia mesh repair (LVHR) is gaining popularity possibly due to reduced complications, reduced hospital stay, early return to work and better cosmesis. In intra-peritoneal onlay method (IPOM) a dual layer composite mesh with an absorbable barrier on the visceral surface is used for minimising bowel adhesions. Three most popular prosthetic mesh scaffolds are polypropylene (PP), polyester and expanded polytetrafluoroethylene (ePTFE). A new generation of monolayer condensed polytetrafluoroethylene (cPTFE) Omyra® mesh, which theoretically has better tissue integration with parietal tissue and possibly lesser adhesions with visceral organs is now available for use. Objective: The aim of our study is to assess the safety and efficacy of Omyra (cPTFE) mesh versus other mesh types in LVHR. Method: We retrospectively collected data from 62 patients who underwent LVHR using cPTFE, as well as other mesh types from January 1, 2011 to December 31, 2020. Patient demographics, Hernia Characteristics, perioperative events, postoperative results and complications were documented and analysed. Results: Among the 62 patients studied, there were 27 (43.55 %) in the Omyra group and 35 (56.45 %) in the other synthetic meshes group. The mean age of the Omyra group was 53.19 (31–85) and 55.03 (22–81) for the other synthetic meshes group. There were no differences in terms of patient demographics and major comorbidities. At presentation, the indication was more commonly for recurrence (p = 0.043), and patients were more symptomatic (p = 0.0034) in the Omyra group than the other synthetic meshes group. There were no differences in mean operating time, post-operative recovery and complications, as well as early (<30 days) and late (>30 days) complications during follow up. Conclusion: The use of cPTFE (Omyra™) mesh yielded comparable operative characteristic compared to other synthetic meshes for LVHR. The rate of perioperative complications and early recurrence was similar between Omyra and other synthetic meshes group.